Abordagem institucional: a FAPESP como ator relevante no campo organizacional de produção científica e tecnológica paulista - Breneizer, Renato Wanderley (2009)
This work falls in the field of organizational studies and has the Institutional Theory as a theoretical basis. The focus of the study is one of the main elements of the Institutional Theory: the concept of organizational field. The Foundation for the Support of Research of the State of São Paulo - FAPESP, to exercise central position in the field of organizational scientific and technological production São Paulo, was chosen for the study. The main objective is to increase knowledge of the Institutional Theory and study, under their view, the role of FAPESP in the organizational field of scientific and technological production paulista. To achieve this goal, we tried to identify the organizational field of activity of FAPESP, studying the institutional relations in this field organizational and study the influence of environmental context in the policy for funding of research adopted by FAPESP. The results showed that all the organizations studied under cognitive systems are related and have common influence of specific providers of financial resources for funding of scientific research.